(untitled) - 1991-; Levi, Taltal; 1956-; Obejas, Achy (New York, 2024)
Both small and full of life, Ellie and a new avocado plant grow up together.
Keywords: Fiction; Crecimiento; Novela juvenil; Aguacates; Fathers and daughters; Padre e hijas; Novela juvenil; Novela juvenil; Fiction; Avocados; Fiction; Growth; Juvenile fiction; Spanish language materials; Juvenile fiction; Fathers and daughters; Juvenile fiction; Avocados; Juvenile fiction; Growth; Picture books